Polymorphisms of the MDR1 gene in the Czech population - Pechandová, K; Buzková, H; Slanar, O; Perlík, F (Folia biologica, 2006)
There exists a marked inter-individual variability of P-glycoprotein expression and activity, which can be of clinical importance due to the large number of drugs that are substrates for the transporter. Previously identified polymorphisms in the MDR1 gene belong to important factors causing this phenomenon. Our aim was to investigate the frequency of major functional SNPs of the MDR1 gene coding for P-glycoprotein in the Czech population. DNA was isolated from whole blood of 189 healthy, young and unrelated subjects (99 females and 90 males, aged from 23 to 28 years). The genotypes of polymorphic positions C3435T, G2677T/A, C1236T and T-76A were determined by PCR-RFLP. Observed allelic frequencies were 56.5%, 46.0%, 0.53%, 44.5% and 37.6% for the alleles 3435T, 2677T, 2677A, 1236T and -76A, respectively. We have found 64 subjects homozygous for 3435T, 42 for 2677T, 40 for 1236T and 31 for -76A alleles. The allelic distribution complies well with Hardy-Weinberg equilibrium. Allelic frequencies of functionally important MDR1 variants are in the Czech population similar to that of other Caucasian populations.
Keywords: Česká republika; ATP Binding Cassette Transporter, Subfamily B, Member 1; Czech Republic; frekvence genu; Gene Frequency; Adult; Male; dospělí; lidé; mužské pohlaví; ženské pohlaví; Female; P-glykoprotein; Humans; polymorfismus genetický; Polymorphism, Genetic